ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI INOVASI MENGUNYAH PEREMEN KARET XYLITOL DAN OBAT KUMUR TERHADAP XEROSTOMIA PADA PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISA DI RUMAH SAKIT BHAYANGKARA TK 1 R. SAID SUKANTO - Mastika Chusnul Khotimah (2022)
Patients undergoing hemodialysis should maintain fluid intake restrictions to prevent fluid overload through fluid restriction. However, this limitation of fluid intake can also cause effects on the patient's body, such as hormonal disorders, social and psychological changes, the emergence of thirst and a symptom of dry mouth due to reduced salivary gland production (xerostomia). The purpose of this study was to determine the effectiveness of chewing xylitol gum and gargling with mouthwash to decrease thirst in chronic kidney failure patients undergoing hemodialysis therapy at Bhayangkara Tk. 1 R. Said Sukanto Hospital. Instruments for measuring dry mouth and thirst were using the Dialysis Thirst Inventory (DTI) and Xerostomia Inventory (XI) questionnaires. The results obtained in providing nursing care for seven days found that xylitol gum and mouthwash were effective in reducing xerostomia in chronic kidney failure patients undergoing hemodialysis. The difference between the two is that xylitol gum has a more significant effect than mouthwash.